The deubiquitinase ataxin-3 requires Rad23 and DnaJ-1 for its neuroprotective role in Drosophila melanogaster - Tsou, Wei-Ling (Neurobiol Dis, 2015)
Ataxin-3 is a deubiquitinase and polyglutamine (polyQ) disease protein with a protective role in Drosophila melanogaster models of neurodegeneration. In the fruit fly, wild-type ataxin-3 suppresses toxicity from several polyQ disease proteins, including a pathogenic version of itself that causes spinocerebellar ataxia type 3 and pathogenic huntingtin, which causes Huntington’s disease. The molecular partners of ataxin-3 in this protective function are unclear. Here, we report that ataxin-3 requires its direct interaction with the ubiquitin-binding and proteasome-associated protein, Rad23 (known as hHR23A/B in mammals) in order to suppress toxicity from polyQ species in Drosophila. According to additional studies, ataxin-3 does not rely on autophagy or the proteasome to suppress polyQ-dependent toxicity in fly eyes. Instead this deubiquitinase, through its interaction with Rad23, leads to increased protein levels of the co-chaperone DnaJ-1 and depends on it to protect against degeneration. Through DnaJ-1, our data connect ataxin-3 and Rad23 to protective processes involved with protein folding rather than increased turnover of toxic polyQ species.